COMPARATIVE STUDY OF ETHIDIUM BROMIDE INTERACTION WITH SYNTHETIC POLYNUCLEOTIDES ds-POLY(rA)-POLY(rU) AND ds-POLY(dA)-POLY(dT) (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
A comparative study on the interaction of classical intercalator ethidium bromide (EtBr) with different nucleic acids (NA) has been carried out. EtBr was revealed to preferentially bind to ds-NA belonging to A-family, rather than to B-family, because the stabilizing effect of this ligand decreases in the following order: ds-poly(rA)-poly(rU), ds-poly(dA)-poly(dT), ds-DNA.
Keywords: DNA, synthetic polynucleotide, intercalator, complex, melting temperature